Home fire sprinkler cost assessment (SpringerBriefs in Fire,, 2014)
This SpringerBrief reviews current home fire sprinkler system costs in one- and two-family dwellings, mobile homes, and multifamily residential buildings up to four stories. It provides individual community data and qualitative data gained through interviews with community officials, builders, and fire sprinkler contractors. The systems are reviewed against a 2008 benchmark study in order to analyze how the increasingly widespread adoption of national sprinkler ordinances impacts system cost. Using 51 homes in 17 communities, the authors discuss the impact of sprinkler ordinances on home fire sprinkler system cost, including extent of coverage, system types, water sources, permit and inspection fees, and statewide requirements. Methods and community comparisons are presented with the analysis. Home Fire Sprinkler Assessment is intended for practitioners working with sprinkler codes and building regulation safety. Researchers working in a related field will also find the book valuable.